2011
DOI: 10.1128/aac.01551-10
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Furamidine Analogues: Influence of Pyridine Nitrogens on Trypanocidal Activity, Transport Kinetics, and Resistance Patterns

Abstract: Current therapies for human African trypanosomiasis (HAT) are unsatisfactory and under threat from emerging drug resistance linked to the loss of transporters, e.g., the P2 aminopurine transporter (TbAT1). Here we compare the uptake and trypanocidal properties of furamidine (DB75), recently evaluated in clinical trials against stage 1 (haemolymphatic) HAT, and two aza analogues, DB820 and CPD0801 (DB829), which are candidate compounds for treatment of stage 2 (neurological) disease. Values of 50% inhibitory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 46 publications
2
71
1
1
Order By: Relevance
“…No saturation could be observed with 28DAP010, whereas in experiments with DB829, saturation was found above 2,000 nM (23). This was probably due to saturation of the P2 transporter with DB829 (23,37). It is possible that 28DAP010 is taken up by an additional high-capacity, low-affinity transporter at high drug concentrations, leading to a stronger drug action at concentrations above 2,000 nM.…”
Section: Discussionmentioning
confidence: 67%
“…No saturation could be observed with 28DAP010, whereas in experiments with DB829, saturation was found above 2,000 nM (23). This was probably due to saturation of the P2 transporter with DB829 (23,37). It is possible that 28DAP010 is taken up by an additional high-capacity, low-affinity transporter at high drug concentrations, leading to a stronger drug action at concentrations above 2,000 nM.…”
Section: Discussionmentioning
confidence: 67%
“…These include the Lister 427 strain in H. P. de Koning's laboratory, TC221 in A. Hofer=s laboratory (a previous gift from F. Opperdoes, Universite Catholique Louvain, Brussels, Belgium), and the multidrug-resistant B48 cell line in which the TbAT1/P2 gene first had been deleted by homologous recombination (TbAT1-KO) (52) and the knockout cells had subsequently been continuously exposed to increasing levels of pentamidine in vitro (33). Reintroduction of the TbAT1 gene in this line created B48 ϩ P2 (17), resulting in a higher-level and more stable expression of the P2 transporter, which appears to be downregulated in vitro when it is expressed only from its original locus (18). Mouse BALB/3T3 fibroblasts (ATCC CCL-163) were cultivated as monolayers at 37°C under a humidified 5% CO 2 atmosphere in Dulbecco's modified Eagle's medium (Sigma) supplemented with 10% (vol/vol) heatinactivated fetal bovine serum, glutamine (0.584 g/liter), and 10 ml/liter of 100ϫ penicillin and streptomycin (Thermo Fisher Scientific [Gibco]).…”
Section: Methodsmentioning
confidence: 99%
“…Experience using this drug for cattle has shown that the trypanosomes rapidly become resistant (16), and specific resistance mutations in the P2 transporter have been experimentally verified (17). Moreover, the P2 transporter has been shown to be the sole transporter for the furamidine trypanocides (18), which until recently were in clinical trials against sleeping sickness (19), and it has also been implicated as one of the main T. brucei transporters for melarsoprol and pentamidine (15,20). A main reason for the easy acquisition of resistance is that the transporter is encoded by a single gene, TbAT1 (5,21).…”
mentioning
confidence: 99%
“…The deoxyadenosine concentrations used here are much higher than what can be expected to occur in the natural environment of the parasites, but it should be remembered that the HMI-9 growth medium contains hypoxanthine as the only purine source, and there is no selective pressure for the parasites to keep the adenosine salvage systems up-regulated. It is, for example, common that in vitro cultivated parasites lose almost all of their P2 nucleoside transporter activity, which transports adenine, adenosine, and deoxyadenosine (32); apparently the transporter is down-regulated under standard culture conditions. Although this does not eliminate all deoxyadenosine uptake, which can also occur by the P1 nucleoside transporter (9), the fact that T. brucei transporters can be differentially expressed under different conditions (33) suggests that in vitro IC 50 values may not necessarily reflect in vivo sensitivities.…”
Section: Discussionmentioning
confidence: 99%